Water–fat MRI for assessing changes in bone marrow composition due to radiation and chemotherapy in gynecologic cancer patients. Issue 6 (28th February 2013) - Bolan, Patrick J.; Arentsen, Luke; Sueblinvong, Thanasak; Zhang, Yan; Moeller, Steen; Carter, Jori S.; Downs, Levi S.; Ghebre, Rahel; Yee, Douglas; Froelich, Jerry; Hui, Susanta
Abstract : Purpose: To assess the feasibility of using fat‐fraction imaging for measuring marrow composition changes over large regions in patients undergoing cancer therapy. Materials and Methods: Thirteen women with gynecologic malignancies who were to receive radiation and/or chemotherapy were recruited for this study. Subjects were imaged on a 3T magnetic resonance (MR) scanner at baseline (after surgery but before radiation or chemotherapy), 6 months, and 12 months after treatment. Water–fat imaging was used to generate high‐resolution, 3D signal fat fraction (sFF) maps extending from mid‐femur to L3. Treatment changes were assessed by measuring marrow sFF in the L4 vertebra, femoral necks, and control tissues. Results: Pretreatment and 6‐month scans were compared in nine women. sFF increased significantly in both the L4 vertebral marrow ( P = 0.04) and the femoral necks ( P = 0.03), while no significant change was observed in control regions. Qualitatively, chemotherapy changes were more uniform in space, whereas the radiation‐induced changes were largest in marrow regions inside and close to the target radiation field. Conclusion: Water–fat MRI is sensitive to changes in red/yellow marrow composition, and can be used for quantitative and qualitative assessment of treatment‐induced marrow damage. J. Magn. Reson. Imaging 2013;38:1578–1584. © 2013 Wiley Periodicals, Inc.